Alcohol reduction strategies among persons with HIV: past attempts, self-reported effectiveness, and future strategies of interest - Nanyangwe Siuluta; Christina E. Parisi; Shantrel S. Candidate; Jacqueline Sherbuk; Yan Wang; Maya Widmeyer; Charurut Somboonwit; Jessy G. Dévieux; Robert L. Cook; Natalie E. Chichetto (Addiction Science & Clinical Practice)
Abstract Background Alcohol consumption is associated with poor health outcomes in people with HIV (PWH). Although various alcohol reduction strategies exist, little is known about PWH’s past experiences or future preferences. This study describes the previous strategies PWH had used, their perceived effectiveness, among people who ever drank, and the strategies PWH who endorsed heavy drinking would consider trying in the future. It also examines how these experiences and preferences vary by sociodemographic factors and past 12 month drug use. Methods A cross-sectional analysis was conducted on data from 453 PWH enrolled in the Florida Cohort Wave III study (2020–2023; mean age 50 years, 60% men). Participants who attempted to reduce or quit drinking (n = 321) were asked about their use of eight alcohol reduction strategies and rated the effectiveness of each on a 4-point Likert scale. Participants reporting heavy drinking (n = 170) were asked about their willingness to try seven strategies in the future. Chi-square and Fisher’s exact tests analyzed differences by sex, age, race/ethnicity, and past 12 month drug use. Results Among the 321 who had ever tried to reduce or quit drinking, endorsed strategies including “on my own”/ complete cessation (80%), prayer (61%), Alcoholics Anonymous (AA) (38%), counseling/therapy (31%), inpatient/outpatient detox (23%), self-monitoring (11%), and medication (7%). The strategies with the highest self-reported effectiveness were for prayer (59%), “on my own”/ complete cessation (58%), and in-patient detox (50%). Prayer was significantly more common among females and non-Hispanic Black or Hispanic participants. Those with past 12 month drug use were significantly more likely to have tried most strategies, except medications or prayer. Among 170 who reported heavy drinking, “on my own”/ complete cessation (43%), AA (24%), and counseling/therapy (21%) were the most endorsed strategies they would try in the future. No significant differences in future preferences were found by demographics, but those with past 12 month drug use showed more interest in formal treatment approaches. Conclusion Commonly used alcohol reduction strategies among PWH were non-medical, easily accessible, and perceived as very effective. Incorporating safe and effective patient-driven methods into treatment guidelines may improve strategy uptake.